Skolēnu nacionālās pašapziņas veicināšana Jāņa Jaunsudrabiņa īsās prozas darbu apguvē literatūras stundās 11.klasē - Antone, Egita (Latvijas Universitāte, 2013)
The aim of the graduation paper The promotion of national selfconfidence of students in the process of studying short stories of Janis Jaunsudrabiņš in the literature classes of form 11 is to make a methodical system to acquire the texts of short stories by Janis Jaunsudrabiņš in literature classes in form 11, thus promoting national selfconfidence of students and creating awareness of ethical values in Latvian cultural environment.After studying the ideas in pedagogical,psychological and methodical literature and investigation of students the methodical system to study short stories by J.Jaunsudrabiņš in form 11 has been made The graduation paper consists of the introduction,five chapters with subchapters,conclusions and appendixes. The first chapter describes the importance of literature classes in the pr omotion of national selfconfidence of students, the second chapter deals with the life and creativity of J.jaunsudrabiņš, the values of his creative works in the context of literature studies. The third chapter describes the preparation of a teacher for literature classes, presents the characterisation of youth age and the class, besides it also describes the methodical system, thematical planning and tasks to acquire the personality and creative works of J. Jaunsudrabiņš in seven literature classes in form 11. The fourth and the fifth chapter describes the process of literature classes and analyses the pedagogical cooperation and the results of classes procedure. The worked out methodical system to acquire short stories by J.Jaunsudrabiņš inliterature classes may help to encourage the national selfconfidence of students both by understanding the diverse personality of the writer and the diversity of ethical and estetical values in his works and their importance in personal development nowadays. The key words: national selfconfidence, short stories, literature classes, values.
Formation of pupils’ national awareness in the process of getting acquainted with Jānis Jaunsudrabiņš creative work in literature lessons in Grade 11
Keywords: Pedagoģija